2014
DOI: 10.1002/2014gl062063
|View full text |Cite
|
Sign up to set email alerts
|

Climate field reconstruction uncertainty arising from multivariate and nonlinear properties of predictors

Abstract: Climate field reconstructions (CFRs) of the global annual surface air temperature (SAT) field and associated global area-weighted mean annual temperature (GMAT) are derived in a collection of pseudoproxy experiments for the past millennium. Pseudoproxies are modeled from temperature (T), precipitation (P), T + P, and VS-Lite (VSL), a nonlinear and multivariate proxy system model for tree ring widths. Spatial patterns of reconstruction skill and spectral bias for the T + P and VSL-derived CFRs are similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 55 publications
3
59
0
Order By: Relevance
“…temperature and soil moisture controls on tree-ring width (e.g. Anchukaitis et al, 2006;Vaganov et al, 2006;Tolwinski-Ward et al, 2011;Evans et al, 2014) or temperature and seawater composition controls on the oxygen isotopic composition of biocarbonates (e.g. Thompson et al, 2011;Russon et al, 2013;Dee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…temperature and soil moisture controls on tree-ring width (e.g. Anchukaitis et al, 2006;Vaganov et al, 2006;Tolwinski-Ward et al, 2011;Evans et al, 2014) or temperature and seawater composition controls on the oxygen isotopic composition of biocarbonates (e.g. Thompson et al, 2011;Russon et al, 2013;Dee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PSMs translate relevant dynamical and isotope variables to modeled proxy space for a direct comparison between GCM output and observations, thereby alleviating the need for a calibration. Thus far, only Evans et al [2014] have used PSM-generated proxies in pseudoproxy reconstructions; using a tree ring width model only, the authors found that the PSM-based reconstructions differed substantially from a standard ''temperature plus noise'' pseudoproxy model. Our study builds on this work by including PSMs for oxygen isotopes in corals and ice cores in addition to tree ring width.…”
Section: Introductionmentioning
confidence: 99%
“…Our study builds on this work by including PSMs for oxygen isotopes in corals and ice cores in addition to tree ring width. Importantly, this study uses PSMs for both the production of the pseudoproxies and their estimation in the DA reconstruction process; this differs from Evans et al [2014] where a PSM for tree ring width was only used for the production of the pseudoproxies. Through a series of experiments reconstructing both surface temperature and geopotential height at 500 hPa, the PSM-pseudoproxy framework serves as a test bed for investigating assumptions concerning our understanding of proxy-temperature relationships, and how errors in these assumptions trickle down to the reconstructed fields.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of the proxy into a climatic variable can be achieved through regression or traditional inverse methods as is done with the widely used regional drought atlases (Cook et al, , 2010aPalmer et al, 2015). Nevertheless, in many cases the multivariate nature of proxy data, the presence of large uncertainties and limited spatiotemporal coverage in a calibration proxy network or nonstationary behavior between the proxy predictor and the climate predictand render regression and inversion challenging (e.g., Wilson et al, 2010;Lehner et al, 2012;Smerdon, 2012;Tingley et al, 2012;Coats et al, 2013a;Gallant et al, 2013;Evans et al, 2014;Konecky et al, 2014;Raible et al, 2014;Wang et al, 2014bWang et al, , 2015Konecky et al, 2016).…”
Section: Expectations Of Temporal or Spatial Consistency Betweenmentioning
confidence: 99%
“…PSMs are forward models and therefore do not require assumptions of local or regional stationarity and linearity that are typically applied in inverse approaches, and they can characterize multivariate influences (Evans et al, 2013;Phipps et al, 2013). Paleoclimate observations in their "native" units may be directly compared to models by using the output variables of simulations or other climate models that have been processed through a PSM to generate simulated paleoclimate observations -sometimes called "pseudoproxies" in the literature (Thompson et al, 2011;Tolwinski-Ward et al, 2011;Smerdon, 2012;Phipps et al, 2013;Evans et al, 2014). PSMs may therefore provide more appropriately analogous comparisons for models and proxies; they also allow for the propagation of uncertainties because PSM-derived estimates of parameter errors and observational random error do not need to be inverted.…”
Section: Expectations Of Temporal or Spatial Consistency Betweenmentioning
confidence: 99%